MUDHARABAH FINANCING RISK MANAGEMENT ANALYSIS STUDY AT BMT SIDOGIRI BONDOWOSO BRANCH - Hosaini Hosaini; Wedi Samsudi; Ubaidillah Ubaidillah; Muzayyahah Muzayyahah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
In Islamic financial institutions, we are familiar with the term mudharabah. In its division, mudharabah is divided into two, namely: the first: Mudharabah muqayyadah which means shahibul maal provides limits on the funds invested. And the second: Mudharabah Muthlaqah shahibul maal does not provide restrictions on the invested funds. The focus of this research is how to implement mudharabah financing at BMT Sidogiri Bondowoso Branch. and how is the risk management strategy of mudharabah financing in BMT Sidogiri Bondowoso Branch. In this study, the author used qualitative research with interview methods, observation methods and documentation methods. So that in the form of analysis we use qualitative descriptive analysis. The results showed that mudharabah financing at BMT Sidogiri Bondowoso Branch was following sharia sharia in sharia economic theory because the terms and conditions had been met, but in mudharabah financing at BMT Sidogiri Bondowoso Branch could only be realized both in the form of raising funds and distributing funds.